Pengaruh Financial Literacy terhadap Sustainability Performance dengan Financial Technology sebagai Variabel Mediasi - Sakti, Windi Pratama; Masdupi, Erni (Jurnal Informatika Ekonomi Bisnis, 2025)
This study aims to examine the effect of financial literacy on sustainability performance with financial technology as a mediating variable in micro, small and medium enterprises (MSMEs) in West Sumatra. This study is a quantitative study with a sample method, namely random sampling. The sample in this study was 297 respondents consisting of micro, small and medium enterprises (MSMEs) in West Sumatra. Data analysis was carried out using the Structural Equation Modeling (SEM) method using IBM SPSS Amos 26 software. The results of this study indicate that Financial Literacy has a significant positive effect on Sustainability Performance. Financial Literacy has a significant positive effect on Financial Technology. Financial Technology has a significant positive effect on Sustainability Performance.